NEXT-TO-LEADING CORRECTIONS AT SMALL-X - Catani, S; Hautmann, F (1995)
We discuss the role of sub-leading corrections to deep inelastic processes in the small-x regime, and report recent results on the calculation of coefficient functions and quark anomalous dimensions.